Aletheia, a new replacement name for Aenigma (Luer) Szlach. & Kolan. (Orchidaceae, Pleurothallidinae) with new combinations - Feng, Zhenhao (Phytotaxa, 2023)
The generic name Aenigma Keller (2017a: 59) was established by the author with two twining species Aenigma patens Keller (2017a: 60) and A. micrantha Keller (2017a: 64) both from Misiones Province, Argentina, belonging to Apocynaceae. In the same year, Keller & Liede-Schumann (2017b) noticed that Bosse (1932: 27) has published a red algae genus, Enigma. To avoid phonetic homonym, the two authors published a replacement name Topea and established a new subtribe Topeinae Keller & Liede (2017b: 134) based on phylogenetic results. Szlachetko et al. (2022: 23) presented new phylogenetic research of Andinia-complex and they decided to elevate the former Andinia subgen. Aenigma (Luer) Karremans & Mark Wilson (2017: 121) to generic rank, namely Aenigma (Luer) Szlachetko & Kolanowska. A new later homonym is made because of unawareness.